Energy and Economic Myths: Institutional and Analytical Economic Essays - Georgescu-Roegen, Nicholas (New York : Pergamon Press, 1976)
This publication covers Four Parts which discuss the: natural resources and the economics of production, institutional economics, epistemology and methodology, and pure theory respectively.
Includes bibliographies and index.
ne 19/04/2018
Loan
Keywords: Economics; Production (Economic theory); Institutional Economics